“Særlig dansk” - Dansk litteraturs kanon i et minoritetsperspektiv - Thisted, Kirsten (Kvinder, Køn & Forskning, 2006)
The Danish Literary Canon (Dansk litteraturs kanon) implicitly addresses pupils of non-Danish origin. The purpose of the canon is to suggest pedagogical tools in the teachings of specific texts that are viewed as central to the Danish and European literary tradition. The consequences of this project are not only that pupils of non-Danish origin become situated as ‘others’ in relation to the idea of ‘danishness’, but that this implicit constitution of ‘same’ and ‘difference’ naturalises Dansih national identity. From a minority studies point of view the pedagogical purpose should be to ask: How to teach Danish literature and with what purpose, and thus, not take what Danish literature is for granted.